Environmental perception by urban school children: influence of green areas, financing and sex in Costa Rica (UNED Research Journal, 2016)
Currently, two main environmental perceptions are recognized: anthropocentrism and ecocentrism. An ecocentric view is associated with childhood, gender and adolescence; nevertheless, there are not studies regarding the effect of school green areas and budget on environmental perception. We analyze the influence of those elements on the environmental perception of 8-9 year old children from eight urban schools in Heredia (Costa Rica). Our survey had 28 statements and questions evaluating contact with green areas, and environmental values, knowledge, attitude and behavior. Ecocentrism dominated in schools with female students or more than 30% green area (X2= 18,5; p=0,002; X2= 14,8, p=0,011). However, boys and girls are both mostly ecocentric, they differ only on the intensity. Budget and total green area were not significant. To encourage sustainable development, an ecocentric perception must be strengthened; green areas must be improved and more attention should be paid to boys’ environmental perception.
Keywords: anthropocentrism; ecocentrism; private schools; public schools; environmental perception; environmental education